2017
DOI: 10.1039/c6cc08404d
|View full text |Cite
|
Sign up to set email alerts
|

Lithium and boron as interstitial palladium dopants for catalytic partial hydrogenation of acetylene

Abstract: It is demonstrated that light elements, including lithium and boron atoms, can take residence in the octahedral (interstitial) site of a Pd lattice by modifying the electronic properties of the metal nanoparticles, and hence the adsorptive strength of a reactant. The blocking of the sub-surface sites to H in the modified materials results in significantly higher selectivity for the partial catalytic hydrogenation of acetylene to ethylene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Our previous work has detailed a method for the synthesis of a stable interstitial species such as smaller Li, B and C elements into Pd lattice after reduction at elevated temperature, which causes detectable Pd lattice expansion due to electron enrichment to Pd. [53][54][55][56] In contrast, we do not see significant change in Ag lattice for Li + doping, even after reduction at the same temperature, presumably the poor catalytic properties of Ag (see Fig. S7-S8 and Table S2; In order to estimate the degree of lithium ion filling in the interstitials within the Ag lattice, using rapid acquisition X-ray pair distribution function, it is possible to characterize the X-ray scattering atoms/ions patterns due to their unique positions of this lattice.…”
Section: Degree Of Octahedral Hole Filling By LImentioning
confidence: 99%
“…Our previous work has detailed a method for the synthesis of a stable interstitial species such as smaller Li, B and C elements into Pd lattice after reduction at elevated temperature, which causes detectable Pd lattice expansion due to electron enrichment to Pd. [53][54][55][56] In contrast, we do not see significant change in Ag lattice for Li + doping, even after reduction at the same temperature, presumably the poor catalytic properties of Ag (see Fig. S7-S8 and Table S2; In order to estimate the degree of lithium ion filling in the interstitials within the Ag lattice, using rapid acquisition X-ray pair distribution function, it is possible to characterize the X-ray scattering atoms/ions patterns due to their unique positions of this lattice.…”
Section: Degree Of Octahedral Hole Filling By LImentioning
confidence: 99%
“…For example, we reported that interstitial lithium doped palladium (Pd− int Li NPs) can be synthesised by heating the mixture of Li(OAc) ⋅ 2H 2 O and Pd/C at elevated temperatures. The Li (nearly metallic) takes residence in structural distorted interstitial sites under hydrogenation conditions, which can completely suppress the formation of the β‐hydride phase and avoid over‐hydrogenation beyond the target ethylene products [13] …”
Section: Figurementioning
confidence: 99%
“…In this work, we have attempted to synthesise Pt−Li NPs according to a previously reported synthetic strategy with limited Li content [13] . With the aid of SXRD (synchotron X‐ray diffraction) and the associated refinement, we report that the unit cell of the Pt metal lattice contracts after lithiation whilst retaining the parent FCC structure.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…More transition metalcatalyzed reactions, however, are controlled by the generation of metastable interstitial atoms [6][7][8][9] . Thus, it is of great interests to explore the control of interstitial site atoms in transition metal catalysts for tuning their catalytic performances [10][11][12] .…”
mentioning
confidence: 99%